(untitled) (KULT_online, 2011)
’Landscape’ has not always been there; it is in the Renaissance that it is first discovered as a concept as such. In constituting landscape, a central role is taken by visual arts and literature: it is due to mediation in arts that landscape becomes a pattern of perception. This study aims at tracing the history of literary ’landscape.’ In doing so the author understands landscape as a natural landscape, and thus he incorporates approaches coming from the aesthetics of nature but without offering new results. The study also focuses on a comparison between literature and visual arts and their possibilities for representing landscape. In an exemplary section, literary landscape is examined in the works of German speaking authors Jean Paul, Adalbert Stifter, Theodor Fontane, and Arno Schmidt. The analyses make clear that landscape as a concept has to be negotiated again and again and that in this context the concept of nature becomes unsound.